2013
DOI: 10.1186/1755-8794-6-49
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of left ventricle and peripheral blood mononuclear cells in a rat model of postinfarction heart failure

Abstract: BackgroundMyocardial infarction (MI) often results in left ventricular (LV) remodeling followed by heart failure (HF). It is of great clinical importance to understand the molecular mechanisms that trigger transition from compensated LV injury to HF and to identify relevant diagnostic biomarkers. The aim of this study was to investigate gene expression in the LV and to evaluate their reflection in peripheral blood mononuclear cells (PBMCs).MethodsMI was induced in rats by ligation of the proximal left coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…We mined four publicly available genome-wide expression data sets from Gene Expression Omnibus (GEO) database in NCBI, including GSE27962 [ 23 ], GSE48060 [ 24 ], GSE7487 [ 25 ] and GSE47495 [ 26 ]. These datasets recorded gene expression data of cardiac remodeling after myocardial infarction or myocardial infarction-induced heart failure.…”
Section: Methodsmentioning
confidence: 99%
“…We mined four publicly available genome-wide expression data sets from Gene Expression Omnibus (GEO) database in NCBI, including GSE27962 [ 23 ], GSE48060 [ 24 ], GSE7487 [ 25 ] and GSE47495 [ 26 ]. These datasets recorded gene expression data of cardiac remodeling after myocardial infarction or myocardial infarction-induced heart failure.…”
Section: Methodsmentioning
confidence: 99%
“…We mined four publically available genome-wide expression data sets from Gene Expression Omnibus (GEO) database in NCBI, including GSE27962 [12], GSE48060 [13], GSE7487 [14] and GSE47495 [15]. These datasets recorded gene expression data of cardiac remodeling after myocardial infarction or Myocardial Infarction-Induced Heart Failure.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…To further explore the functional evidence of the six genetic predispositions that contribute to MACE, we searched all literatures referring to the six genes and cardiovascular diseases in PubMed database. Meanwhile, we also mined several publicly available genome-wide expression data sets from the GEO database, [12][13][14][15] which recorded cardiac remodeling data after myocardial infarction (MI). We found two of six genes, MYOM2 and ECHS1, showed abundant evidences of decreased expression in cases with adverse cardiac events, either in previous reports or in our data analysis.…”
Section: Biological Implications Of Variants Associated With Macementioning
confidence: 99%
See 1 more Smart Citation
“…BTHS standard of care currently includes administration of medications, such as diuretics and angiotensin-converting enzyme (ACE) inhibitors—there is currently no disease-modifying therapy for this disorder 12 . In addition, previous studies have indicated that cardiac TAZ mRNA expression is diminished in several heart failure animal models, chronic human heart failure patients, and human patients with dilated cardiomyopathy, suggesting that tafazzin expression influences both BTHS and common heart failure 3, 14, 15, 16, 17, 18…”
Section: Introductionmentioning
confidence: 99%